Analisis Geometris Sistem Kendali Elevator Pesawat Udara N219 - Lenny Iryani; Arie S Ramadhan (METAL: Jurnal Sistem Mekanik dan Termal, 2021)
Flight control of elevator are used to control the attitude of the aircraft in pitching configuration. The system of this flight control are controlled by the force given by a pilot so that the aircraft will move to the desired pitch condition. In this research the force that should be inputted by a pilot easily and smooth are analyze. The study of this analysis was using N219 airplane designed by PT. Dirgantara Indonesia. The preliminary design of the force that should be inputted by a pilot are in 495 kN.mm. The result of the study are shown that the length of the arm in the elevator system give Margin of Safety in a range of 3 – 4.